2019
DOI: 10.1038/s41598-019-52550-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism Detection in Photovoltaic Backsheets by Fully Convolutional Neural Network

Abstract: Materials and devices age with time. Material aging and degradation has important implications for lifetime performance of materials and systems. While consensus exists that materials should be studied and designed for degradation, materials inspection during operation is typically performed manually by technicians. The manual inspection makes studies prone to errors and uncertainties due to human subjectivity. In this work, we focus on automating the process of degradation mechanism detection through the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In accelerated lab tests, specific aging factors are analyzed for simulating environmental operating conditions 14–17 . A more recent approach uses fully convolutional neural networks to explain BS degradation 18 . First studies have been reported that bridge the gap between accelerated aging test in the lab and natural degradation in the field 2,19–24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accelerated lab tests, specific aging factors are analyzed for simulating environmental operating conditions 14–17 . A more recent approach uses fully convolutional neural networks to explain BS degradation 18 . First studies have been reported that bridge the gap between accelerated aging test in the lab and natural degradation in the field 2,19–24 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] A more recent approach uses fully convolutional neural networks to explain BS degradation. 18 First studies have been reported that bridge the gap between accelerated aging test in the lab and natural degradation in the field. 2,[19][20][21][22][23][24] These studies comprise single observations though and lack the combination and transformation of the individual results to operating conditions in the PV power stations.…”
mentioning
confidence: 99%
“…Accordingly, some FDAs or technologies based on string current are proposed. Then, based on the current string characteristics, the paper proposes a PVA outlier detection (OD) algorithm combining "threshold method Hampel identifier (HI)" for mismatch detection and location [28][29][30].…”
Section: Pva-oriented Online Monitoring Systemmentioning
confidence: 99%
“…Gradual recognition of the fact that the degradation behavior of PV-module BSs depends strongly on the BS composition resulted in focused attention on BS failures specific for different polymer materials [1,2]. For example, many reports discuss particular issues of PAbased BS, including "chalking" (titania deposits), massive cracks in the BSs, a loss of mechanical strength and wet leakage resistance as well as potential reasons for degradation of PA-BSs [12][13][14]. In these studies, most analyses are carried out for single PV-modules in test labs.…”
Section: Introductionmentioning
confidence: 99%